The concept of "literary genre"and its didactics in Compulsory Education textbooks - Bartolomé Porcar, Cristina (Didáctica. Lengua y Literatura, 2025)
The concept of "literary genre", despite its complexity, is integrated into the training of students in the subject of Spanish Language and Literature, due not only to the preceding didactic tradition, but also to its usefulness in systematizing the continuum of works, facilitating reading comprehension and serving as a model for creativity. The aim of this paper is to understand precisely how the explanation of this important term is approached by analyzing textbook material as an observable "sign" of classroom work. Specially, a sample of thirty-two Compulsory Secondary Education texbooks from eight publishers was used for the aforementioned subject. The content of their pages has been studied quantitatively and qualitatively to examine how the presentation of genres is organized, the discourse used in the definitions and, finally, the activities that accompany them. The results obtained show that the main emphasis is on their classificatory function and, to a lesser extent, their role in interpretation and creation of texts. The activities reinforce the recognition of forms through the identification and comparison of features, although they also include creative tasks.